(untitled) (Scientific journal of the Fergana State University, 2026)
This article presents a comparative analysis of the common features in the lives and creative works of Alisher Navoi and Zahiriddin Muhammad Babur. It examines their literary heritage, including poetic and prose works, as well as their activities as prominent statesmen and cultural figures. Particular attention is paid to their contributions to the development of classical literature and to their aesthetic and artistic views as reflected in various literary genres. The article also explores how Navoi and Babur demonstrated their knowledge and artistic mastery in the fields of art, history, music, and broader cultural life.